Evaluation of anti-citrullinated and anti-carbamylated antibodies in mexicans with rheumatoid arthritis and at-risk individuals - Edgar E. Lara-Ramírez; Betzaida Cuevas-Córdoba; Diana Olguín-Calderon; Yadira Bastian; César Ramos-Remus; José D. Castillo-Ortiz; Martín Zapata-Zúñiga; Jesús Núñez-Contreras; Leendert A. Trouw; José A. Enciso-Moreno; Julio E. Castañeda-Delgado (Revista de Investigación Clínica)
Background: Rheumatoid arthritis (RA) diagnosis is a challenge in the initial phases of the disease when clinical symptoms are only starting to develop. Early diagnosis and treatment can promote long-term remission, reduce disability, and improve cardiovascular outcomes. Autoantibodies can help in the diagnosis and identification of RA patients in the early phases of the disease, but scarce information has been reported for the Mexican population. Objective: To study anti-citrullinated peptide antibodies (anti-CCP) and anti-carbamylated protein antibodies (anti-CarP) in Mexican patients with RA and individuals at high risk of developing the disease. Methods: Serum samples from long-standing and early RA patients, first-degree relatives (FstD) of RA patients, and healthy individuals were analyzed for anti-CCP and anti-CarP using enzyme-linked immunosorbent assay. Results: Anti-CCP and anti-CarP levels were higher in the RA groups than in the FstD and healthy groups. The odds ratio (OR) for anti- CCP for RA groups was 29.7 (95% confidence interval [CI] 14.2-61.9), significantly higher than the OR for anti-CarP 11.07 (95% CI 5.4-22.8). The sensitivity of anti-CCP was 85% (95% CI 76-93) higher than for anti-CarP (42.1%, 95% CI 31-54). The specificity of anti-CarP was 93.8% (95% CI 90-97) and the specificity of anti-CCP was 83.4% (95% CI 78-88). Using both tests in parallel increased sensitivity to 91%, while a sequential approach increased sensitivity to 98%. Conclusion: Anti-CCP outperformed anti-CarP in Mexican RA patients, demonstrating greater sensitivity, while anti-CarP showed higher specificity. Combining these tests, either simultaneously or sequentially, could enhance diagnostic accuracy.